Prospective surveillance of Zika virus at the end of the Americas’ outbreak: An unexpected outcome - Rivas, Enrique; Ojeda, Joyce; Garcia-Rivera, Enid J.; Rivera, Doris M.; Arredondo, José L.; Medina, Eduardo López; Aguirre, Floriberto; Bernal, Luis; Chen, Zhenghong; Petit, Celine; Guranathan, Sanjay; Heinrichs, Jon H.; et al. (Frontiers in Tropical Diseases, 2022)
Objective The French Polynesia Zika virus (ZIKV) outbreak (2013–2014) broadened the known manifestations of ZIKV disease (ZVD) to include neural and congenital syndromes. A subsequent epidemic in the Americas (2015–2016) caused >685,000 suspected/confirmed cases before seemingly disappearing as fast as it expanded. A study was implemented (2017–2018) to detect ZVD cases in the region (Mexico, Honduras, Colombia and Puerto Rico), with the aim of validating surveillance methodology so as to increase sensitivity in case detection, which would have potential application for future vaccine development endeavors. Study design and setting To identify potential cases, we focused on signs/symptoms that were frequently associated with ZVD for confirmation by PCR. Serostatus and seroconversion were evaluated by ZIKV non-structural protein 1 blockade-of-binding enzyme-linked immunosorbent assay (BOB ELISA) and microneutralization assay. Results Overall, 2,400 participants aged 15–40 years were enrolled; 959 (40.0%) had signs/symptoms that could be associated with ZVD: axillary temperature ≥37°C (64.3%), myalgia (60.8%) and arthralgia (58.6%). Three suspected cases were virologically confirmed. Zika seroprevalence was high at study initiation (52.6% [BOB ELISA] and 56.0% [microneutralization assay]). In participants who were Zika seronegative, low seroconversion rates were observed after one year follow-up (3.6% [BOB ELISA] and 3.1% [microneutralization assay]). Conclusion The ZIKV continued to circulate in the Americas at very low levels following the 2015–2016 outbreak. The epidemiological factors driving Zika’s rapid rise and decline remain poorly understood. Clinical trial registration Clinicaltrials.gov: NCT03158233 BARDA (Contract # HHSO100201600039C) WHO Universal Trial Number: U1111-1183-5687.